Vakum Norma Status dan Pengelolaan Aset Daerah Hasil Kerja Sama Pemerintah Pusat dan Daerah Pasca Pemekaran Wilayah - Shella Yulianingsih; I Dewa Gede Herman Yudiawan (Pemuliaan Keadilan, 2026)
Regional decentralization within the framework of regional autonomy in Indonesia often creates a regulatory vacuum regarding the ownership and management of assets resulting from cooperation between the central and regional governments. This study aims to analyze the provisions of Law No. 23 of 2014 on Regional Government and to identify regulatory gaps and models for resolving conflicts over public assets following decentralization. The research method employed is a normative legal approach using legislative, conceptual, case-based, and comparative analyses. The findings reveal that Law No. 23/2014 does not explicitly regulate the status of assets during the agreement period, mechanisms for the transfer of rights and obligations, ownership proportions from multi-source financing, or compensation for the parent region. Consequently, legal uncertainty arises regarding large-scale strategic assets involving third parties. This study also found that multi-party mediation involving the governor and the prosecutor’s office proved more effective in resolving public asset disputes than litigation, as demonstrated in the Tasikmalaya case. This study recommends revising Law No. 23/2014 by adding a special chapter on the transfer of assets resulting from post-decentralization cooperation and formalizing the involvement of the prosecutor’s office in the mediation of public asset disputes.